AB1328 Characterizing norwegian rheumatoid arthritis patients using the quest-ra protocol for comparison with other european countries. (23rd January 2014) - Haugeberg, G.; Wilberg, E.R.; Gjelberg, H.K.; Rødevand, E.; Isler, T.S.
Abstract : Background: The QUEST-RA project (Quantitative Standard Monitoring of Patients with Rheumatoid Arthritis) a multi centre and multinational project has revealed significant differences in disease severity and treatment in RA patients in European countries (1, 2). Norway joined QUEST-RA in 2009. Objectives: To compare Norwegian RA patients with other European countries using the QUEST-RA protocol. Methods: From two ordinary rheumatology outpatient clinics in Norway (Kristiansand and Trondheim) 200 consecutive RA patients 100 from each centre using the QUEST-RA protocol was included. Data on demographics, disease severity and treatment was collected. Data collection was finished spring 2010. Continuous variables are presented as mean (SD) or median [range]. Results: Demographic: age 58 (13) years, females 65.5%, BMI 25.7 kg/m 2, Caucasian 98.5%, current smoker 26.6%, education 11.0 [4-20] years, full time employed 17.1%, full time employed age <65 years 25.0%, disease duration 13.3 (10.9) years. Disease activity: DAS28 3.6 (1.4), 28 joint count swollen 1.0 [0-21] and tender 3.0 [0-28], doctors global 1.8 [0-7.7] mm, ESR 14 [2-78] mm/hr. Patient reported outcomes measures (PROMs): HAQ 0.88 [0-2.63], pain 3.5 [0-9.3] cm, fatigue 3.8 [0-10] cm, patient global 3.8 [0-9.8] cm, morning stiffness 45.0 [0-301] min. Disease markers: RF+ 73.1%, erosive status 61.5%. Treatment: biologics 27.0%, methotrexate 59.5%, other DMARDs 14.0%, prednisolone 52.0%. Significant (p<0.05) gender differences (men/women) were found for the following variables: full time employed <65 years (47.7%/14.1%), DAS28 (3.1/3.9), HAQ (0.50/0.88). No significant gender differences were found for e.g. swollen joints, ESR, RF and erosions and treatment. In comparison with other European QUEST-RA countries disease activity and health status in Norwegian RA patients were comparable with countries that had reported the lowest disease activity (DAS28) and the best health status in their RA patients (see table below). The proportion of RA patients treated with biologics in Norway is among the highest in Europe. Conclusions: Norway is among European countries reporting the lowest level of disease activity in their RA patients and is also among countries with the highest proportion of patients on biologics. This however cannot be explained by use of biologics alone as e.g. Finland (1) using significant less biologics than Norway is reporting even a lower disease activity in their RA patients. References: Sokka T et al. Ann Rheum Dis. 2007;66:1491-6. Sokka T et al. Ann Rheum Dis. 2009;68:1666-72. Disclosure of Interest: G. Haugeberg Grant/Research support from: Abbott Norway, E. Wilberg: None Declared, H. Gjelberg: None Declared, E. Rødevand: None Declared, T. Isler Grant/Research support from: Abbott International